A functional RNA/DNA circuit for one-pot detection of SARS-CoV-2 RNA. Issue 97 (16th November 2022) - Li, Dayong; Cheng, Wenting; Hou, Zhiqiang; Duan, Chengjie; Yao, Yanheng; Chen, Yan; Yang, Gang; Cheng, Zhouxiang; Xiang, Yang
Abstract : Integrating the nucleic acid circuit technology and CRISPR/cas12a system for one-pot detection of SARS-CoV-2 RNA. Abstract : A simple method is proposed in this work for the detection of SARS-CoV-2 RNA based on a functional RNA/DNA circuit. By ingeniously integrating the nucleic acid circuit technology and CRISPR/cas12a system, this method can achieve femtomolar detection of the target RNA in one step and successfully distinguish COVID-19 positive cases from clinical samples, proving its great potential for clinical application.